A COMPARATIVE STUDY OF MULTI-MASTER REPLICATION OF NOSQL DATABASE SERVER WITH VARYING DATA FORMATS - Wibowo, Dwi Kurnia; Darmawan, Agus; Nawangnugraeni, Devi Astri (Jurnal Teknik Informatika (Jutif), 2025)
NoSQL Databases are currently an effective solution for managing large data sets distributed across many Servers. NoSQL Database design is usually based on its usability. Specifically related to the system or application to be built. This research aims to measure the Transfer Rate, CPU usage, Memory usage, query execution time for Create, Insert, Delete and remote replication query bandwidth in the Multi-Master Server replication process using two document stored NoSQL Database applications namely CouchBase and CouchDB by entering three different data models namely JSON, XML and CSV. The experimental results show that the Transfer Rate with CSV data format on CouchBase has the lowest value with an average of 111.41 kbps. CPU usage with XML data format on CouchBase has the lowest value with an average of 13.89%. Memory usage with JSON data format on CouchBase has the lowest value with an average of 1.68%. Query Execution Time Create with XML data format on CouchBase has the lowest value with an average of 1.16 seconds. Query Execution Time Insert on CouchBase with CSV data format has the lowest value with an average of 33.28 seconds. Bandwidth Query Execution Time Insert with CSV data format on CouchBase has the lowest value with an average of 24.78 mb. Query Execution Time Delete with JSON, XML and CSV data formats on CouchDB has the lowest value with an average of 1.5 seconds. Further research recommendations are to test Multi-Master Server Replication using other data formats and parameters or test the performance of data migration to other Databases with different data formats.